2016
DOI: 10.1097/icu.0000000000000286
|View full text |Cite
|
Sign up to set email alerts
|

Antivascular endothelial growth factor in the treatment of retinopathy of prematurity

Abstract: Although anti-VEGF therapies show promise in the treatment of ROP, frequent reoccurrences and lack of thorough data about long-term side effects of pharmacologic intervention necessitate further research before anti-VEGF agents become the mainstay of ROP management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…For many years, laser treatment has been the 'gold standard' in infants suffering from ROP. [8][9][10] Besides a more detailed evaluation of the questions listed above, it is of great interest if there are other growth factors than VEGF that are involved in pathological neovascularization in the course of ROP, and if their inhibition would have an additional effect on preventing neovascularization. 5,6 Nevertheless, anti-VEGF medication was increasingly applied during the last years, in particular by using bevacizumab and ranibizumab that have been already used in other neovascular diseases in the back of the eyes since the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For many years, laser treatment has been the 'gold standard' in infants suffering from ROP. [8][9][10] Besides a more detailed evaluation of the questions listed above, it is of great interest if there are other growth factors than VEGF that are involved in pathological neovascularization in the course of ROP, and if their inhibition would have an additional effect on preventing neovascularization. 5,6 Nevertheless, anti-VEGF medication was increasingly applied during the last years, in particular by using bevacizumab and ranibizumab that have been already used in other neovascular diseases in the back of the eyes since the last 10 years.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, some questions about the long-term outcome compared to conventional laser treatment are still not answered, for example, about development of myopia, vascular changes or size of the visual field, and stage of ROP has also to be considered. [8][9][10] Besides a more detailed evaluation of the questions listed above, it is of great interest if there are other growth factors than VEGF that are involved in pathological neovascularization in the course of ROP, and if their inhibition would have an additional effect on preventing neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…Intravitreal injections of Anti- VEGF (Vascular Endothelial Growth factor) are increasingly being employed in eyes with Retinopathy of Prematurity (ROP), ever since the BEAT-ROP study highlighted the efficacy of intravitreal Bevacizumab in the management of stage III plus ROP. [12] Of all the anti-VEGF agents, Bevacizumab has been employed the maximum in ROP with several studies including comparison with laser photocoagulation which is the standard of care, available in the literature. [34] Aflibercept (EYLEA; Regeneron Pharmaceutical Inc, Tarrytown, NY, USA and Bayer, Basel, Switzerland), also named VEGF Trap-eye, has been employed in ROP, previously as monotherapy in 26 eyes.…”
mentioning
confidence: 99%
“…91,92 Following the publication of the first prospective BEAT-ROP (Efficacy Study of Intravitreal Bevacizumab for Stage 3+ Retinopathy of Prematurity), which demonstrated the efficiency of the monoclonal antibody bevacizumab, anti-VEGF agents have been increasingly used as first-line treatment or as second-line treatment at certain stages and locations of the ROP. 93 The VEGF family plays a major role in angiogenesis, with VEGF-A having an important influence on this process. 94 Among the agents that inhibit vascular endothelial growth factor are agents that partially block VEGF-A and agents that perform a pan-blockade of VEGF-A.…”
Section: Current Therapies Of Ropmentioning
confidence: 99%